Ketamine-induced bladder syndrome: Recognition as a key differential diagnosis and the need to curb recreational use (Indian Journal of Case Reports, 2025)
The recreational use of ketamine is becoming increasingly widespread, largely due to its dissociative and anesthetic properties, as well as its accessibility and affordability. A significant and often irreversible impact on the urinary system has recently emerged as a concerning consequence of its recreational use. We present a case report of a young man who has been using ketamine recreationally for less than a year and has developed ketamine bladder syndrome. Within a few months, the patient developed acute kidney injury and some liver damage, as indicated by his blood tests, while continuing to take ketamine.